Biochemical characterization of Peumus boldus fruits: Insights of its antioxidant properties through a theoretical approach. (15th February 2022) - Otero, Carolina; Miranda-Rojas, Sebastián; Llancalahuén, Felipe M.; Fuentes, Juan A.; Atala, Cristian; González-Silva, Gloria; Verdugo, Diego; Sierra-Rosales, Paulina; Moreno, Adrián; Gordillo-Fuenzalida, Felipe
Highlights: Biochemical analysis of fruits from Peumus boldus. Peumus boldus fruits from Region of Maule, Chile were used to prepare an extract. Extract was analyzed by different techniques to know its biochemical properties. Computational electrochemical calculation of redox potential and oxidation mechanisms of the extract compounds. The study will help to understand the benefits of the P. boldus fruit consumption. Abstract: Peumus boldus is an endemic tree species from Chile whose leaves have been the focus of study for decades given that their infusions are reported to relieve rheumatic symptoms, headache, dyspepsia, urinary tract inflammation, and symptoms of other illnesses. These health properties have been studied mainly using leaves and bark, then it is relevant to know more about these properties in different parts of the plant. Considering the importance of P. boldus fruits in the diet of some rural populations, we analyzed their properties to explore its impact on the Chilean population health. Liquid chromatography and mass spectrometry analysis confirmed the presence of alkaloids such as boldine, although aporphine N -methyl-laurotetanine was the most abundant. In addition, flavonoids catechin, chrysin and quercetin were also found in the extract. Cytotoxicity and anti-inflammatory activities of the fruit extract were invitro tested by using a murine macrophage cell model, observing that a diluted fraction of the extract was not cytotoxic, but showed anti-inflammatory activity, which is likely attributed to antioxidants activities. By means of quantum chemical calculations, we calculated the redox potential of the respective alkaloids and flavonoids found in the extract. Results suggest a synergistic effect between alkaloids and flavonoids, where boldine and N -methyl-laurotetanine showed similar antioxidant properties. Finally, we present a description of the oxidation mechanisms for both groups of molecules which will sustain P. boldus fruit biological properties, in order to give this kind of fruits scientific value focusing on human health.